TECHNOLOGY TRANSFERS FOR DEVELOPMENT AND OPERATION OF MESOPHILIC BIODIGESTERS WITH MANUAL AGITATION - Carlos SABORÍO VÍQUEZ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
According to the needs of small farmers and indigenous population in their communities, a study was conducted to determine the best alternative applicable to this people; the study is based on the production of renewable energy in the form of biogas produced by mesophilic biodigesters. They were compared between different types of digesters used throughout the history of the production of biogas and determined to be the best choice in the field of biogas production to the areas mentioned above is that of innovation digesters having a system of manual agitation, which enables durability of the bacterial mass provided by the even greater biomass in a digester without agitation, which in turn increases the service life of the digester, and also takes into account the needs of the population of interest and resources.